2015
DOI: 10.1590/0103-6440201300115
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Susceptibility In Vitro Determined by the Etest(r) for Candida Obtained from the Oral Cavity of Irradiated and Elderly Individuals

Abstract: This study aimed to evaluate the in vitro antifungal susceptibility of Candida species of head-and-neck-irradiated patients (Group 1), non-institutionalized (Group 2) and institutionalized elders (Group 3) using Etest® methodology. Candida was isolated from saliva and presumptively identified by CHROMagar Candida(r), confirmed by morphological criteria, carbohydrate assimilation (API 20C AUX®) and genetic typing (OPE 18). The collection was made from 29, 34 and 29 individuals (Groups 1, 2 and 3, respectively) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Biofilms are defined as microbial communities encased in a matrix of extracellular polymeric substance (EPS), which display phenotypic features that differ from their planktonic or free-floating counterparts (3)(4)(5). It is known that C. glabrata exhibits intrinsically low susceptibility to azoles and develops resistance after exposure to these drugs (6) and C. krusei is naturally resistant to fluconazole, but in most cases, it is sensitive to voriconazole (cross-resistance is uncommon in this specie) (7,8), which complicates the treatment of candidiasis caused by this species. Because of that, it is important to know the behavior of these species when they grow together in a biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms are defined as microbial communities encased in a matrix of extracellular polymeric substance (EPS), which display phenotypic features that differ from their planktonic or free-floating counterparts (3)(4)(5). It is known that C. glabrata exhibits intrinsically low susceptibility to azoles and develops resistance after exposure to these drugs (6) and C. krusei is naturally resistant to fluconazole, but in most cases, it is sensitive to voriconazole (cross-resistance is uncommon in this specie) (7,8), which complicates the treatment of candidiasis caused by this species. Because of that, it is important to know the behavior of these species when they grow together in a biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…to traditional antifungal drugs. The increasing microbial resistance rates may also be a result of long-term drug exposure or selection of strains with intrinsic resistance mechanisms (Fernandez-Ruiz et al, 2015;Freitas et al, 2015;Liao et al, 2015;Seifi et al, 2015;Ying et al, 2013). Therefore, the development of novel strategies to minimize the toxic effects of current antifungals and improve their effectiveness has been strongly encouraged.…”
Section: Introductionmentioning
confidence: 99%
“…Lalla et al and Ramierez‐Amador et al also showed that oral fungal presence increased during radiotherapy for oral cavity and pharyngeal tumors. Emerging strains of Candida species that are resistant to antifungal medicines have been reported, perhaps establishing the need to determine the susceptibility of clinical isolates …”
Section: Discussionmentioning
confidence: 99%
“…Emerging strains of Candida species that are resistant to antifungal medicines have been reported, perhaps establishing the need to determine the susceptibility of clinical isolates. 22 Many of the current regimes for antifungal treatment of CRN are borrowed from the treatment of oral and oropharyngeal candidiasis. Recommendations range from nystatin and other topical therapies that are swallowed to systemic treatment for more severe infections.…”
Section: Discussionmentioning
confidence: 99%